Building with the on-site manufacturing process - N. Pattanajan; A. Suddeepong; S. Horpibulsuk (International Association of Lowland Technology, 2018)
In general, the process of building construction makes the inevitable wastes such as nails, formwork, steel and concrete. In order to reduce these wastes, parts of building have therefore been produced by using the manufacturing process. This process can improve construction process with minimum wastes and time of construction. However, the manufacturing process is not completely effective for building construction. There is also an additional cost for the transportation from manufactory to the construction site. For this reason, to set the exact time of the construction process, to avoid material waste and to effectively reduce the construction cost, all the production processes of manufacturing building should be started and ended at construction sites. This research has studied the Lean Manufacturing Process (LMP) and applied to the process of the construction which is called “the building with the on-site manufacturing process, BMP” to reduce instable human resource by machines which provides three advantages as follows: 1) the better quality, 2) minimum constructing cost and 3) minimum constructing period.